Computational fluid dynamics analysis of air velocity and temperature distribution in an air-conditioned office - Yi, Huilin (2018)
In this Final-Year project, the thermal environment of an air-conditioned office is analysed by computational fluid dynamics (CFD). In order to investigate the characteristics of both velocity and temperature distributions at different locations of inlet and outlet vents inside the room, the four types of configurations are modelled for CFD simulations. The first case places the inlet and outlet vents at the upper zone of two opposite walls, which is named “Up-in with Up-out”. The second case provides the inlet at the bottom area of a wall and the outlet at the upper area of the opposite wall, which is called “Up-in with Down-out Op”. The third case puts the inlet and outlet at the same side of a wall, which is named “Up-in with Down-out”. The last case places the inlet at the bottom area of a wall and the outlet at the upper area of the opposite wall, which is named “Down-in with Up-out”. All case studies are separately conducted by changing the inlet airflow velocity, temperature and direction. The simulations are carried out at steady state in two-dimensional (2D) and three-dimensional (3D) domains. From simulation results, it is shown that Cases 1, 2 and 3 can achieve thermal comfort, and Case 4 needs further to improve for optimization of the indoor air quality.